PERAN ASSOCIATION OF SOUTHEAST ASIAN NATIONS (ASEAN) DALAM MENANGANI ANCAMAN TERORISME DI KAWASAN ASIA TENGGARA TAHUN 2016-2021 - Fatimah Zahara; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ASEAN stated that terrorism was very dangerous. Terrorist attacks kill innocent people, damage infrastructure, destroy the environment, and hinder ASEAN from achieving its goals. In 2016-2021, ASEAN stated that the threat of terrorism was growing, such as cooperation between regional groups and ISIS groups, the return of foreign fighters, and the emergence of single terrorists. The author examines the role of ASEAN in dealing with terrorism in the Southeast Asian region in 2016-2021. In this research, the writer used descriptive qualitative method. The author used literature and interviews in collecting primary and secondary data. Primary data was obtained through official ASEAN website sources, and interviews with the Ministry of Foreign Affairs, while secondary data was obtained from journal articles, the internet, books, etc. which were then processed according to the topic of discussion. This study usedthe perspective of Pluralism and the theory of the Role of International Organizations. The results of the study show that ASEAN plays a dominant role as an arena in dealing with terrorism, namely facilitating discussion and cooperation through the ASEAN Defense Minister's Meeting (ADMM), ASEAN Regional Forum (ARF), and ASEAN Ministerial Meeting on Transnational Crime (AMMTC) mechanisms to produce documents that serve as guidelines in tackling terrorism in the Southeast Asian region. ASEAN also cooperates with Russia and Australia in dealing with terrorism. The impact of ASEAN's role, namely terrorism attacks in the Southeast Asian Region, has decreased. Keywords: ASEAN, Terrorism, Southeast Asia Region